2019
DOI: 10.1103/physrevb.100.205135
|View full text |Cite
|
Sign up to set email alerts
|

ARPES study of orbital character, symmetry breaking, and pseudogaps in doped and pure Sr2IrO4

Abstract: Sr2IrO4 is characterized by a large spin-orbit coupling, which gives rise to bands with strongly entangled spin and orbital characters, called J 1/2 and J 3/2 . We use light-polarization dependent ARPES to study directly the orbital character of these bands and fully map out their dispersion. We observe bands in very good agreement with our cluster dynamical mean-field theory calculations. We show that the J 1/2 band, the closest to the Fermi level EF , is dominated by dxz character along kx and dyz along ky. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Combining the TB model with qualitative modeling of the photoemission matrix elements, we trace the measured dichroism to the tilted real-space character of the relevant orbitals. The intrinsic dichroism is found to be particularly sensitive to the orbital character, which is beyond standard LDAD based on the anisotropy of the photoemission intensity upon rotating the light polarization direction by 90°1 7,19,20 . Hence, iLDAD is a powerful addition to the toolbox of dichroism in ARPES, in the spirit of going beyond band structure mapping and gaining information about energy-and momentumresolved electronic wavefunction of solids.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Combining the TB model with qualitative modeling of the photoemission matrix elements, we trace the measured dichroism to the tilted real-space character of the relevant orbitals. The intrinsic dichroism is found to be particularly sensitive to the orbital character, which is beyond standard LDAD based on the anisotropy of the photoemission intensity upon rotating the light polarization direction by 90°1 7,19,20 . Hence, iLDAD is a powerful addition to the toolbox of dichroism in ARPES, in the spirit of going beyond band structure mapping and gaining information about energy-and momentumresolved electronic wavefunction of solids.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, disentangling extrinsic and intrinsic contributions is of capital importance to access the additional information encoded in the photoemission matrix elements. Important examples include gaining insights into the orbital character of the electronic band structure in solids [17][18][19][20][21] , the chirality of charge carriers 22,23 , quantum geometric properties, such as orbital pseudospin texture 24,25 as well as Berry curvature [26][27][28][29] . The orbital texture in TMDCs is very sensitive to the lattice structure and collective effects such as charge density waves (CDW) [30][31][32][33][34] and the debated excitonic insulator state [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…The existence of NB states could also solve the puzzle of the pseudogap observed in Rh-doped metallic state [8,9]. We have shown that the pseudogap is not restricted to the region near k F , but is on the contrary clearest at X , where only incoherent weight is expected [21]. This becomes natural if the pseudogap is due to a distorsion of the line shape near E F , created by the underlying structure of NB states, that would be for Rh close to the metallic band but possibly remaining distinct.…”
mentioning
confidence: 79%
“…These markers are reported in Fig. 3(c) and compared to the dispersion measured by ARPES in the pure compound [21], to which they are nearly identical. On the other hand, there are three new bands appearing closer to the Fermi level, emphasized as color markers.…”
mentioning
confidence: 82%
See 1 more Smart Citation